Elite Dental Students: a Cross-Sectional Study on Different Aspects of Their Life-Style - Abdolhamid Zafarmand; Maryam Asvar (Shiraz University of Medical Sciences, 2017)
Statement of the Problem: Lifestyle has a key role in having a life with quality. This is much more critical in academic community. Elite students are the scientific capital of each community; therefore, improvement of their life-style is a very crucial issue and is a way of esteeming them. Purpose: This study was aimed to scrutinize the life-style of elite dental students to provide a guideline for healthy life-style for their own and for other students, as well. Materials and Method: This descriptive and cross-sectional study was carried out on 115 Elite dental students, from a list 175 students, based upon their interest. The HPLP-II questionnaire was used which focuses on 6 behavioral fields: Spiritual Growth, Interpersonal Relations, Nutrition, Physical Activity, Health Responsibility, and Stress Management. The results also compared genders and marital status within the study group. The elite dental students were categorized in 3 age groups as 19≥ yrs (Group I), 20-22 yrs (Group II), and 23≤ yrs. (Group III) for comparison. Data were analyzed using SPSS version 19, independent t-test, one-way ANOVA, and Tukey's test. Results: The mean score of the HPLP-II questionnaire was 2.51±0.27 (out of score 4). Spiritual growth (2.85±0.42) and physical activity (2.16±0.58) were the highest and the lowest scores, respectively. Physical activity was the only subscale different between genders (p= 0.000). Marital status had not effect on life-style of students. Between the age groups, the physical activity was significantly different between group I and II (0.002). Conclusion: Elite dental students' life-style is most prominent in spiritual growth and interpersonal relationships dimensions, but is the weakest in physical activity and health responsibility behavioral attitudes. To improve the talent of all students, interventional workshops/courses aiming at modification and promotion of students' lifestyle is recommendable in the curriculum.